2023
DOI: 10.1002/oby.23736
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of semaglutide versus liraglutide for treating post‐metabolic and bariatric surgery weight recurrence

Abstract: Objective The aim of this study was to compare the effectiveness of semaglutide versus liraglutide for treating post‐metabolic and bariatric surgery (MBS) weight recurrence. Methods A retrospective analysis of 207 adults with post‐MBS weight recurrence treated with semaglutide 1.0 mg weekly (n = 115) or liraglutide 3.0 mg daily (n = 92) at an academic center from January 1, 2015, through April 1, 2021, was conducted. The primary end point was percentage body weight change at 12 months of treatment with regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Similar results were reported in a recent retrospective study on post-MBS patients who were prescribed semaglutide or liraglutide after 8 years [47]. Significant weight loss was achieved 12 months after the initiation of pharmacotherapy and the weight loss was higher in the semaglutide group than in the liraglutide group [47].…”
Section: Effects Of Glp-1-receptor Agonists (Glp-1-ra) In Patients Af...supporting
confidence: 86%
“…Similar results were reported in a recent retrospective study on post-MBS patients who were prescribed semaglutide or liraglutide after 8 years [47]. Significant weight loss was achieved 12 months after the initiation of pharmacotherapy and the weight loss was higher in the semaglutide group than in the liraglutide group [47].…”
Section: Effects Of Glp-1-receptor Agonists (Glp-1-ra) In Patients Af...supporting
confidence: 86%
“…16,19 Two observational studies by Bonnett and Murvelashvili each reported that among patients with prior bariatric surgery, semaglutide can achieve 9 – 13% weight loss with a year of treatment. 20,21 In order to realize the potential of adjuvant AOM, rigorous studies are needed to develop practice guidelines that direct the use of AOMs as adjuvant therapy. This includes clearly defining suboptimal response to bariatric surgery and obesity disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Reoperation can be beneficial for some patients but may carry increased perioperative risk compared to primary surgery [ 95 , 96 ]. Anti-obesity medications (AOMs) may also be effective therapeutically for weight recurrence and suboptimal postsurgical weight loss [ 31 , [97] , [98] , [99] ]. Moreover, adjunctive use of AOMs may halt the trajectory of post-bariatric weight recurrence [ 100 ], with potential implications for the prevention of this particular complication.…”
Section: Discussionmentioning
confidence: 99%